CIVIL LAW AND CRIMINAL LAW ASPECTS OF HOAX NEWS IN ELECTRONIC MEDIA - rafiqi rafiqi; maswandi maswandi; marsella marsella (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The advancement of information technology (internet) and allforms of benefits in it brings its own negative consequences whichare increasingly troubling the community. The abuse that occursin this cyber space is what is then known as cyber crime orInformation Technology and Electronic other regulators use theterm computer crime. The formulation of the problem in this studyis how the aspects of Civil Law and Criminal Law of Hoax newsElectronic Media How Efforts in Identifying the Spread of Fake /Hoax News as a Form of Cyber Crime in Indonesia. The researchmethod in this writing uses Normative Juridical, the nature of thisresearch is prescriptive research. The results of the discussion inthis study are aspects of civil law and criminal law ElectronicMedia Hoax News In Article 1372 of the Civil Code states thatcivil suits regarding defamation are aimed at obtainingcompensation and restoration of honor and good name. Themeasure used to determine whether a person's actions haveoffended honor is very broad. The difference between the regulationof fake news in Law Number 1 of 1946 concerning Criminal LawRegulations and the regulation of fake news regulated in LawNumber 11 of 2008 and Law Number 19 of 2016 concerningInformation and Electronic Transactions is that Articles 14 and15 do not mention what kind of fake news, while the Informationand Technology Law is more detailed in mentioning fake news inthe context of electronic transactions and speech that causeshatred. Efforts to Identify the Spread of Hoaxes as a Form of CyberCrime in Indonesia The Chairperson of the Indonesian Anti-HoaxSociety, Septiaji Eko Nugroho provides 5 simple steps that can helpin identifying hoaxes and which are real news, the followingexplanation Be careful with provocative titles, Look at the siteaddress, Check the facts, Check the authenticity of photosParticipate in anti-hoax discussion groups.I. IntroductionThe advancement of internet technology has led to new